Effect of Modified Atmosphere Packaging on the Shelf Life and Postharvest Quality of Purple Passion Fruit (Passiflora edulis Sims - Yumbya, Peninah; Ambuko, Jane; Shibairo, Solomon; Owino , Willis O (Journal of Postharvest Technology, 2014)
Passion fruit (Passiflora edulis Sims) being highly perishable is  susceptible to rapid water loss after harvest leading to  diminished quality. This study evaluated the efficacy of  activebag® which is a new modified atmosphere packaging  (MAP) product in the Kenyan market. Fruits harvested at 60-65  and 75-80 days after anthesis were either packaged in  activebag® or ordinary polyethene bags and allowed to ripen  under ambient room conditions. MAP maintained the quality of  fruits harvested at both stages of maturity and prolonged their  shelf life by at least 14 days compared to the unpackaged  controls. Packaging significantly slowed weight loss, which was  lower at 7% compared to the unpackaged controls that lost up to  26% of the weight. Both MAP packages reduced ethylene  production and respiration rate and slowed other  physicochemical changes associated with passion fruit ripening.  Although the ordinary polythene bag packaging prolonged the  fruits’ shelf life compared to unpackaged control, their positive  effect was negated by high incidence of rotting evident after 14  days of storage. These results indicate that use of activebag®  can prolong the shelf life by maintaining quality attributes and  external appearance of purple passion fruits and hence extend  their marketing period.
Keywords: Activebag®; Ethylene; Respiration; Water loss; Physicochemical